2020
DOI: 10.3390/ijms21186753
|View full text |Cite
|
Sign up to set email alerts
|

Ligation-Mediated Polymerase Chain Reaction Detection of 8-Oxo-7,8-Dihydro-2′-Deoxyguanosine and 5-Hydroxycytosine at the Codon 176 of the p53 Gene of Hepatitis C-Associated Hepatocellular Carcinoma Patients

Abstract: Molecular mechanisms underlying Hepatitis C virus (HCV)-associated hepatocellular carcinoma (HCC) pathogenesis are still unclear. Therefore, we analyzed the levels of 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG) and other oxidative lesions at codon 176 of the p53 gene, as well as the generation of 3-(2-deoxy-β-d-erythro-pentafuranosyl)pyrimido[1,2-α]purin-10(3H)-one deoxyguanosine (M1dG), in a cohort of HCV-related HCC patients from Italy. Detection of 8-oxodG and 5-hydroxycytosine (5-OHC) was performed by li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Artificial intelligence (AI), a field of computer science that mimics human intelligent behavior and performs tasks that commonly require human intervention, has gained interest in the field of cancer research for its problem solving, decision making and pattern recognition abilities [ 16 ]. Machine learning (ML) and deep learning (DL), two subsets of AI, have emerged as important tools that could effectively improve the field of molecular cancer characterization, from epidemiology [ 17 ], to diagnosis, prognosis and patient classification [ 18 ], with higher performance than traditional approaches [ 19 , 20 , 21 , 22 , 23 , 24 ]. Accumulating evidence suggests that radiomics can be used to study tumor heterogeneity and to predict therapy in CRC [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence (AI), a field of computer science that mimics human intelligent behavior and performs tasks that commonly require human intervention, has gained interest in the field of cancer research for its problem solving, decision making and pattern recognition abilities [ 16 ]. Machine learning (ML) and deep learning (DL), two subsets of AI, have emerged as important tools that could effectively improve the field of molecular cancer characterization, from epidemiology [ 17 ], to diagnosis, prognosis and patient classification [ 18 ], with higher performance than traditional approaches [ 19 , 20 , 21 , 22 , 23 , 24 ]. Accumulating evidence suggests that radiomics can be used to study tumor heterogeneity and to predict therapy in CRC [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…DNA damage, unless fully repaired, can lead to mutations, including in oncogenes and tumor suppressors, initiating the process of carcinogenesis [5]. Moreover, we provide evidence that the generation of DNA damage at a single nucleotide resolution causes characteristic signatures at the site of mutations along the TP53 sequence, indicating a causal relationship between DNA damage and cancer [13,14].…”
Section: Introductionmentioning
confidence: 73%
“…They are considered to be a reliable biomarker of carcinogen exposure [7,8] and cancer risk [9,10]. Recently, we indicated that the generation of DNA damage at single nucleotide resolution causes characteristic signatures at the site of mutations along the sequence of the tumor suppressor gene TP53 (TP53), indicating a causal relationship between DNA damage and human cancer [11,12]. In addition to genotoxic effects, air pollution can cause various epigenetic alterations, as on the levels of DNA methylation and non-coding RNA transcripts [1], important regulators for gene transcription [13].…”
Section: Introductionmentioning
confidence: 99%